PATIENT ASSESSMENT OF INTERPERSONAL QUALITY IN OUTPATIENT INSTALLATION CLINIC HOSPITAL EYE UNDAAN - Finda Muthia Hanum (Universitas Airlangga, 2020)
The mission of Undaan Eye Hospital is to provide high quality and affordable eye health service. However, some problems which indicate customer’s dissatisfaction are still found, including the amount of customer complaints which hasn’t reached the target set by hospital which is zero complaint. Based on Customer Complaint Report of Undaan Eye Hospital, most complaints are caused by communication problem. The aim of this study is to analyze the interpersonal quality of Polyclinic of Outpatient Clinic of Undaan Eye Hospital which consists of respect, confidentiality, courtesy, responsiveness, dan empathy. This study is using descriptive and cross-sectional design and conducted to 82 people who are representing the outpatients and proceeded using simple random sampling method. The data were obtained by interviewing respondents using questionnaire. The data is analyzed using quantitative method and presented in tables. The result of the study shows that most of the respondents which includes 63,41% respondents feeling a little satisfied with interpersonal quality in Polyclinic of Outpatient Clinic of Undaan Eye Hospital. The result of the study shows that most of respondents feeling satisfied with respect, courtesy, confidentiality, and empathy of the service, however they are feeling a little satisfied with responsiveness of the service. Therefore, the hospital needs to improve their quality especially in responsiveness aspect by reducing patient wait times, and maintaining the quality of the aspects which have good ratings of patient satisfaction.Keywords: interpersonal quality, outpatient clinic, patient satisfaction